Polisitemia Sekunder pada Pasien Laki-Laki Muda dengan Sindrom Nefrotik - Wardhani, Ariani Intan; Nugroho, Pringgodigdo; Rinaldi, Ikhwan; Sarasawati, Meilania; Miranda, Monik Ediana; Harahap, Agnes Stephanie (Jurnal Penyakit Dalam Indonesia, 2025)
Polycythemia is a condition characterized by an abnormal increase in the total red blood cell mass and is classified into primary and secondary polycythemia. Secondary polycythemia occurs as a physiological response to tissue hypoxia or increased erythropoietin production, without intrinsic abnormalities in erythroid progenitor cells. This condition is rare, particularly when associated with nephrotic syndrome. This report aims to describe a case of secondary polycythemia associated with focal segmental glomerulosclerosis (FSGS). A 20-year-old man presented with generalized edema for five months prior to admission, accompanied by foamy urine. Physical examination revealed peripheral edema and minimal ascites. Laboratory investigations demonstrated massive proteinuria and elevated hemoglobin levels. Renal biopsy confirmed the diagnosis of FSGS, while bone marrow biopsy showed normocellular findings without evidence of malignancy or fibrosis. The patient was treated with methylprednisolone, ramipril, and simvastatin, and underwent four sessions of phlebotomy along with antiplatelet therapy. Following treatment, there was improvement in hemoglobin levels, proteinuria, and blood pressure control. Secondary polycythemia has been reported to be associated with various parenchymal kidney diseases, including FSGS. The proposed mechanisms include increased erythropoietin production due to renal ischemia or dysregulation of erythropoiesis feedback mechanisms. Phlebotomy is an important therapeutic intervention to prevent complications related to hyperviscosity and thromboembolism and has been shown to result in clinical improvement. This case illustrates a rare occurrence of secondary polycythemia in a patient with nephrotic syndrome due to FSGS. Accurate diagnosis and comprehensive management, including phlebotomy, can lead to meaningful clinical improvement. This report is expected to contribute to the literature on the diagnosis and management of secondary polycythemia in kidney disease.